From Working in the Fields to Taking Control: Towards a Typology of Women's Decision-Making in Wheat in India - Farnworth, Cathy Rozel; Jafry, Tahseen; Bharati, Preeti; Badstue, Lone B.; Yadav, Ashok (Springer, 2021)
Women in India perform a range of roles in wheat-based agricultural systems. However, data remain sparse. Cultural norms which construct men as farmers serve to conceal women’s contributions from researchers and rural advisory services. We use data from communities in four Indian states, selected to exemplify high and low gender gaps, to provide insights into how women are challenging norms which privilege male decision-making in order to participate in innovation processes. We hypothesized the transitioning of women from labourers in wheat to innovators and managers of wheat is likely to be far from straightforward. We further hypothesized that women are actively managing the processes unleashed by various sources of change. We use the concept of doxa—ideas and actions in a society that are taken for granted and are beyond questioning—as an analytic lens to help us understand the ways in which women deploy their agency to secure their goals. Our analysis allows us to develop a ‘A typology of women’s strategies to strengthen their managerial decision-making power in wheat’.